The Role of Social Media in Driving Consumer Spending and Fostering Brand Loyalty - Evar, Kiren; Hidayat, Rahmat; Haq, Saiful (Scieclouds Publishing, 2023)
This research focuses on the influence of social media presence on the consumer’s buying behavior and their allegiance to the brands which are represented on platforms such as Facebook, Instagram or TikTok. Because social media is now becoming one of the most important marketing platforms, it is important to understand how it impacts a consumer’s decision. Survey research method was used and cross-sectional quantitative approach was used whereby data was collected from 500 actively using social media users aged 18-45 years. The interaction between SM interaction, buying behavior, and brand patronage was determined using descriptive and inferential statistics such as Pearson correlation, Multiple regression and ANOVA. To recap the findings, the study shows that the overall interaction with social media through multiplied advertisements, endorsement by influentials, and active use of brand content is very much positively linked to consumers’ expenditure and brands’ steadiness. Furthermore, the investigation proved that the sharing platforms like Instagram and TikTok, which provide more of the picture and video content, have a stronger impact on the client’s impulsive buying and short-term behavior compared to the traditional media. Further, brand communities and customized customer engagements through the social media platforms played central roles in creating lasting customer relationship and customer loyalty. This research indeed tries to fill the foregoing lacuna in the literature by providing the empirical investigation into the correlation between social media consumption and consumers thus underlining the relevancy of the interactive communication and digital marketing for maintaining customer continuity and loyalty. These insights are useful for any organizational entity who would like to implemented social media as a marketing tool for promotional campaigns as well as customer retention.